Knowledge, attitudes and practices about influenza vaccination among pregnant women and healthcare providers serving pregnant women in Managua, Nicaragua - Arriola, Carmen S. (Vaccine, 2018)
BACKGROUND: Nicaragua implemented an influenza vaccination program for pregnant women with high-risk obstetric conditions in 2007. In 2014, the recommendation of influenza vaccination expanded to include all pregnant women. Given the expansion in the recommendation of vaccination, we evaluated knowledge, attitudes and practices of pregnant women and their healthcare providers towards influenza vaccination and its recommendation. METHODS: We conducted surveys among pregnant women and their healthcare providers from June to August 2016 at two hospitals and 140 health facilities in Managua. The questions were adapted from the U.S. national CDC influenza survey and related to knowledge, attitudes and practices about influenza vaccination and barriers to vaccination. We analyzed reasons for not receiving vaccination among pregnant women as well as receipt of vaccination recommendation and offer by their healthcare providers. RESULTS: Of 1,303 pregnant women enrolled, 42% (5 4 5) reported receiving influenza vaccination in the 2016 season. Of those who reported not receiving vaccination, 46% indicated barriers to vaccination. Pregnant women who were vaccinated were more likely to be aware of the recommendation for vaccination and the risks of influenza illness during pregnancy and to perceive the vaccine as safe and effective, compared to unvaccinated pregnant women (p-values < 0.001). Of the 619 health workers enrolled, over 89% recalled recommending influenza vaccination to all pregnant women, regardless of obstetric risk. Of the 1,223 women who had a prenatal visit between the start date of the influenza vaccination and the time of interview, 44% recalled receiving a recommendation for influenza vaccination and 43% were offered vaccination. Vaccination rates were higher for those receiving a recommendation and offer of vaccination compared with those who received neither (95% vs 5%, p-value < 0.001). CONCLUSION: Pregnant women in Managua had positive perceptions of influenza vaccine and were receptive to receiving influenza vaccination, especially after the offer and recommendation by their healthcare providers.